Contrasting Responses of Marine and Freshwater Photosynthetic Organisms to UVB Radiation: A Meta-Analysis - Jin, Peng; Duarte, Carlos M.; Agustí, Susana (Frontiers in Marine Science, 2017)
Ultraviolet-B (UVB) radiation is a global stressor that has profound impacts on freshwater and marine ecosystems. However, an analysis of the patterns of sensitivity to UVB radiation across aquatic photosynthetic organisms has not yet been published. Here, we performed a meta-analysis on results reported in 214 studies compiled from the published literature to quantify and compare the magnitude of responses of aquatic photosynthetic organisms to changes in UVB radiation. The meta-analysis was conducted on observations of marine (n = 893) and freshwater macroalgae (n = 126) and of marine (n = 1087) and freshwater (n = 2889) microalgae (total n = 4995). Most of these studies (85%) analysed the performance of organisms exposed to natural solar radiation when UVB was partially or totally reduced compared with the organismal performance under the full solar radiation spectrum, whereas the remaining 15% of the studies examined the responses of organisms to elevated UVB radiation mostly using artificial lamps. We found that marine photosynthetic organisms tend to be more sensitive than freshwater photosynthetic organisms to UVB radiation; responses to either decreased or increased UVB radiation vary among taxa; the mortality rate is the most sensitive of the trait responses to elevated UVB radiation, followed by changes in cellular and molecular traits; the sensitivity of microalgae to UVB radiation is dependent on size, with small-celled microalgae more sensitive than large-celled microalgae to UVB radiation. Thick macroalgae morphotypes were the less sensitive to UVB, but this effect could not be separated from phylogenetic differences. The high sensitivity of marine species, particularly the smallest photosynthetic organisms, to increased UVB radiation suggests that the oligotrophic ocean, a habitat comprising 70 % of the world’s oceans with high UVB penetration and dominated by picoautotrophs, is extremely vulnerable to changes in UVB radiation.